Conceptual modifications of coal preparation plants to minimize potential environmental issues associated with coal waste disposal. (15th August 2019) - Rezaee, Mohammad; Rajagopalan, Venkat N.; Honaker, Rick Q.
Highlights: Coal waste streams were studied to minimize potential environmental impacts. Conductivity screening and acid-base accounting tests were performed. Less 10% of materials cause elevated conductivity of supernatant. Segregation and isolation of such fractions minimizes release of elements. Modifications to preparation plants and waste disposal practices were formulated. Abstract: An environmental concern at coal preparation operations is the release of elements resulting from the oxidation or dissolution of certain minerals contained in the process waste streams. Using a standard conductivity test, the electrical conductivity (EC) of water samples obtained from mixing with various particle size and density fractions of a given plant waste material were measured as an indicator of total dissolved solids. The net neutralization potential (NNP) of the fractions were also measured to predict the pH of the supernatant upon disposal. As a result, the particle size and density fractions contributing to high EC levels were identified with the objective of potentially extracting and isolating these fractions which can significantly reduce the negative environmental impacts. The results showed that the EC generated from coarse refuse streams were significantly higher than the values obtained from fine refuse streams. Based on the NNP values, the coarse refuse stream generates highly acidic pH, while the fine refuse in contact with water produces circumneutral pH. Furthermore, the high specific gravity (>2.68) fractions which comprised less than 10% of the coal waste streams were found to be the primary source of elevated EC levels. The remaining fractions were found to be of minimal environmental concern. Based on the obtained results, modifications to the coal preparation plants were proposed to minimize the environmental concerns of coal waste disposal. Modifications include pyrite removal from the spiral refuse and desulfurization of flotation feed and sieve bend underflow streams using low-cost mineral spiral circuitry. After the segregation, the pyrite (high density) fraction, which encompasses around 1% of the coarse and fine refuse streams, will be isolated/encapsulated and the fine refuse stream dewatered and co-disposed with the coarse refuse stream. The proposed modifications to the processing and disposal practices not only minimize the generation of acid mine drainage thereby reducing the release of trace elements and EC of the discharged water, but also enhances the recovery and quality of the final clean coal product.